Integrating TQM Practices And Knowledge Management To Enhance Malaysian Digital Banking - Fam, Soo Fen; Husseini, Saleh Ali (Universidad del Zulia, 2019)
Purpose-The purpose of this study is to develop an integrated model of total quality management (TQM), knowledge management (KM) for Malaysian digital banking financial crime mitigation to enhance bank reputation. Design/methodology/approach-The quantitative study has been carried out in Malaysian banks. Data were collected from 100 employees the executive management team level and above in banks dyads working in Malaysia and is analyzed through structural equation modeling technique using SPSS 22.0 and SmartPLS 2.0. Findings-The results reveal that Integrating Total Quality Management Practices and Knowledge Management Processes helped in Enhancing Malaysian Digital Banking Reputation, which combat financial crimes through strengthening its anti-money laundering and terror financing capabilities, so as to maintain their global competitive edge in this domain. Research limitation/recommendation – the study is only focusing on the digital banking service in Malaysia. There have digital bank where are different with digital banking and also digital banking service in Malaysia might have some different compared to other countries. Hence, there have not standardization of digital banking to be measured. Practical implications – This Findings of study can be utilized by banks to Enhance digital banking reputation, which has been identified as a key to growth and development. Originality/value This study complements the previous researches and seeks to extend literature in digital banking. Malaysia still in earlier stage of adopting digital banking. Hence, reputation can influence decision and confidence of customer.